Intelligent approaches to performance support - Ashok Banerji; Stephen Richards; Philip Barker (Association for Learning Technology, 1994)
Electronic performance support systems provide an important method of meeting on-demand educational and training requirements. They also provide efficient and effective ways of enabling the knowledge and expertise within an organization to be shared. This paper discusses the design of a distributed electronic performance support system and the ways in which 'intelligent agents' based on expert systems and neural networks can be used to locate and share distributed expertise. A case study illustrating our approach to the implementation and use of intelligent agents is presented.